1974
DOI: 10.1161/01.str.5.5.630
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Changes in Pa CO 2 Cerebral Blood Volume, Blood Flow, and Vascular Mean Transit Time

Abstract: Abstract:The O-labeled water. Over this range of Paco,, a significant linear relationship of CBV = 0.041 Paco, + 2.0 was found. For each one torr change in Paco,, there is a change in CBV of 0.041 ml/100 gm of perfused tissue. At a normocarbic value of Paco, (~37 torr), an average value of 3.5 ml/100 gm was found. A nonlinear relationship of CBV and CBF was found. This relationship is expressed in the equation, CBV = 0.80 CBF 038 . A significant linear relationship was found between CBF and Paco,. This was des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

44
646
4
4

Year Published

1989
1989
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 988 publications
(706 citation statements)
references
References 51 publications
44
646
4
4
Order By: Relevance
“…This is in close accordance with the range 0.18-0.36 determined by several groups using recent techniques such as laser Doppler flowmetry and optical imaging in brain activation studies (Mandeville et al, 1999;Jones et al, 2001; Sheth et al, 2004a and references therein, Leung et al, 2009;Boas and Payne, 2009). Note that the original value ϕ = 0.38 was experimentally determined by Grubb et al (1974) in PET studies using a prolonged hypercapnia challenge in primates.In addition, it is interesting to note that the mean transit time variation is non-monotonic ( Fig. 2D): an initial decrease in the mean transit time is observed because the blood volume initially increases more slowly than the regional blood flow (consistent with the values of ϕ obtained above).…”
supporting
confidence: 87%
“…This is in close accordance with the range 0.18-0.36 determined by several groups using recent techniques such as laser Doppler flowmetry and optical imaging in brain activation studies (Mandeville et al, 1999;Jones et al, 2001; Sheth et al, 2004a and references therein, Leung et al, 2009;Boas and Payne, 2009). Note that the original value ϕ = 0.38 was experimentally determined by Grubb et al (1974) in PET studies using a prolonged hypercapnia challenge in primates.In addition, it is interesting to note that the mean transit time variation is non-monotonic ( Fig. 2D): an initial decrease in the mean transit time is observed because the blood volume initially increases more slowly than the regional blood flow (consistent with the values of ϕ obtained above).…”
supporting
confidence: 87%
“…However, it is not clear why the changes in PETCO2 were significantly different between the three tasks (no change in PETCO2 for MA) but led to very similar changes in [O2Hb] and StO2. This is unexpected since PaCO2 and CBF are almost linearly correlated in the normal physiological range [11]. Thus, the hemodynamic and oxygenation changes cannot solely be explained by PaCO2.…”
Section: Discussionmentioning
confidence: 92%
“…These vessels may also expand due to the increased pressure, further increasing the CBV. Experimental studies (Grubb et al, 1974) have indicated that the steady-state relationship between CBF and CBV can be described with a power law:…”
Section: Physiological Relationshipsmentioning
confidence: 99%
“…In the original formulation of the balloon model (Buxton et al, 1998c), the outflow was modeled as a pure function of blood volume v. Steady-state experiments (Grubb et al, 1974), altering CBF with inhaled CO 2 , found that the steady-state relationship between CBF and total blood volume was well described by an empirical power law (Eq. (1)).…”
Section: The Balloon Modelmentioning
confidence: 99%